The Effect of Discipline, Office Facilities, and Work Environment on Employee Performance - Wahyu Surya Putra; Andriani Andriani (Universitas Negeri Gorontalo, 2026)
Purpose: Employee performance is a critical factor in determining organizational success, particularly in the public sector. However, challenges such as low work discipline, inadequate office facilities, and less conducive work environments are still prevalent. In addition, inconsistencies in previous studies regarding the dominant factors influencing employee performance highlight the need for further empirical investigation. Therefore, this study aims to analyze the effects of work discipline, office facilities, and work environment on employee performance and to identify the most dominant factor.Design/Methodology/Approach: This study employed a quantitative approach with an explanatory research design. The study involved 125 employees as respondents, who were selected using a purposive sampling technique. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the effects of discipline, office facilities, and work environment on employee performance.Findings: The results indicate that work discipline, office facilities, and work environment positively and significantly influence employee performance. Among these variables, work discipline exerts the strongest effect, followed by the work environment and office facilities. These findings demonstrate that both internal and external organizational factors shape employee performance. Therefore, strengthening employee discipline, improving workplace facilities, and fostering a supportive work environment are essential strategies for enhancing organizational performance.